2019
DOI: 10.1146/annurev-chembioeng-060718-030312
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Use of Microfluidics to Study Crystallization Fundamentals

Abstract: This review compares droplet-based microfluidic systems used to study crystallization fundamentals in chemistry and biology. An original high-throughput droplet-based microfluidic platform is presented. It uses nanoliter droplets, generates a chemical library, and directly solubilizes powder, thus economizing both material and time. It is compatible with all solvents without the need for surfactant. Its flexibility permits phase diagram determination and crystallization studies (screening and optimizing experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…Q d = 0. Consequently, the system of equations ( 1)-( 7) can be solved for stationary solutions, cancelling the timederivatives in eqn ( 1) and (7), and parametrizing the volume of the liquid meniscus with its quasi-static equivalent radius Rm , instead of using time t in eqn (4b). This QS approach thus facilitates the parametrical analysis and allows to provide an explanation to the underlying mechanism behind the drop formation.…”
Section: Quasi-static Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Q d = 0. Consequently, the system of equations ( 1)-( 7) can be solved for stationary solutions, cancelling the timederivatives in eqn ( 1) and (7), and parametrizing the volume of the liquid meniscus with its quasi-static equivalent radius Rm , instead of using time t in eqn (4b). This QS approach thus facilitates the parametrical analysis and allows to provide an explanation to the underlying mechanism behind the drop formation.…”
Section: Quasi-static Approachmentioning
confidence: 99%
“…On the one hand, it can be observed that, for a quasi-static meniscus, streamlines are tangent to the meniscus revealing the quasi-static character of the flow, i.e. the righthand side term of eqn (7) and thus set to zero, i.e. Q d = 0.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, droplet microfluidics 1 5 has become an important tool for many different applications, including fundamental studies on emulsification 6 , crystallization 7 and chemical reaction 8 , temperature-controlled tensiometry 9 , molecules encapsulation 10 , particle synthesis 11 , biochemical assays 12 , immunoassays 13 , digital PCR 14 , directed evolution 15 , drug discovery 16 , single-cell analysis 17 or cell and gene manipulations 18 , 19 . Nowadays, all the commercially available and most of lab-made droplet generators are based on a flow-focusing technology implemented in rectangular microchannels fabricated by lithography, and made of polydimethylsiloxane (PDMS), polymers or glass.…”
Section: Introductionmentioning
confidence: 99%